Rivers development: the view of the youth - Abu Samah, Bahaman; Md. Yassin, Sulaiman; Abu Samah, Asnarulkhadi; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
This study attempts to identify the relationship of the rural youth with Pahang and Muar Rivers. This is a quantitative study and used developed questionnaire for collecting its data. A total of 165 rural youth settled along Pahang and Muar Rivers have been selected as the respondents. Findings have confirmed that a majority of rural youth still needs the rivers for their recreational activities while a small portion of them still rely on the river for their additional income. The rural youth have demonstrated a high level of agreement on river development as it offers them benefits with regard to locals’ development, environmental awareness, social bonding and transportation. Further, analysis performed have confirmed that factor of state have recorded significant difference with agreement towards river development while the factor of distance to the nearest city have recorded a positive and significant relationship with agreement towards river development. A number of discussions have been placed and it is a hope that such discussion will assist in any planning of developing Pahang and Muar Rivers.